2014
DOI: 10.1097/cej.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise during pregnancy reduces risk of mammary tumorigenesis in rat offspring

Abstract: Breast cancer is the most common cancer among women. Emerging research indicates that modifying lifestyle factors during pregnancy may convey long-term health benefits to offspring. This study was designed to determine whether maternal exercise during pregnancy leads to reduced mammary tumorigenesis in female offspring. Pregnant rats were randomly assigned to exercised and sedentary groups, with the exercised group having free access to a running wheel and the sedentary group housed with a locked wheel during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Therefore, these preliminary data suggest that maternal exercise can reduce offspring mammary cancer risk (6). Camarillo et al hypothesized that maternal metabolism or factors released into the maternal circulation in response to exercise could lead to programming changes in the offspring, however, there is currently no data to support this claim (6). Future work should seek to elucidate the mechanisms by which protective effects of maternal exercise during pregnancy on offspring breast cancer risk occurs.…”
Section: Cancermentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, these preliminary data suggest that maternal exercise can reduce offspring mammary cancer risk (6). Camarillo et al hypothesized that maternal metabolism or factors released into the maternal circulation in response to exercise could lead to programming changes in the offspring, however, there is currently no data to support this claim (6). Future work should seek to elucidate the mechanisms by which protective effects of maternal exercise during pregnancy on offspring breast cancer risk occurs.…”
Section: Cancermentioning
confidence: 93%
“…Mammary tumor development in all pups was monitored for 15 weeks. These data revealed that offspring from mothers who exercise during pregnancy have a mammary tumor incidence of 42.9% compared to 100% incidence in sedentary offspring (6). Therefore, these preliminary data suggest that maternal exercise can reduce offspring mammary cancer risk (6).…”
Section: Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Ovarian weight was greater in light but not heavy neonates from exercised gilts Maternal exercise increased labeling index in heavy compared with light offspring in fetal but not neonatal or adolescent ovaries 60 Female Sprague Dawley rats Maternal exercise throughout pregnancy Pups from exercised dams had reduced mammary tumor incident after being placed at weaning on a HFD and exposed at 6 weeks of age to the carcinogen, N-methyl-N-nitrosourea…”
Section: Maternal Exercise and Offspring Behavioral And Reproductive mentioning
confidence: 99%